Exploring the Nexus of Inventive Passion on Effectuationand Product Innovativeness (Journal of Asian Development Studies, 2024)
This study investigates the interplay between inventive passion and the effectuation process's role inbringing product and service innovativeness. This research examines the mediating effect ofeffectuation in connection with the entrepreneurial inventive passion product and serviceinnovativeness in SMEs. The study is causal and cross-sectional; SPSS version 26 is used forstatistical inference, whereas Hayes macro version 4.2 is employed for regression analysis. Thefindings suggest that inventive passion has a significant positive relationship with productinnovativeness and effectuation. Furthermore, effectuation mediates the relationship betweeninventive passion and product innovativeness. The study results have considerable implications forentrepreneurs and policymakers seeking to foster innovation and entrepreneurship. In a dynamic anduncertain environment, SMEs can employ compelling logic of effectuation to innovate products andservices. Effectual elements provide the framework for developing the echo system for product andservice inventiveness for passionate entrepreneurs which will facilitate product and serviceinnovativeness